Artificial intelligence and digital forensics: a powerful alliance. A bibliometric review - Rincón, Hildebrando Castañeda; López, Brayan; Otálora, Jorge Hernando Ruiz; Pertuz, Johemir Jesús Pérez (Journal of Posthumanism, 2025)
This article offers a bibliometric review of scientific production related to the use of artificial intelligence in digital forensic analysis between 2013 and 2024. Drawing from 70 academic and technical sources, the study identifies publication trends, leading authors, influential journals, collaboration networks, and documented cases in Colombia. The findings reveal a growing and evolving field that not only advances in technical terms but also engages with legal and ethical discussions. While the academic output has increased steadily, regulatory gaps, limited institutional continuity, and low regional visibility remain significant challenges. The article concludes by recommending the consolidation of a national research agenda and encouraging a more critical and ethically grounded integration of emerging technologies in judicial contexts.